Pengaruh Bahan Pengisi Cangkang Kelapa Sawit Komposit-Silicone Rubber Dalam Permulaan Pemohonan Listrik - Fitriah, Fitriah; Kurnianto, Rudi; Rajagukguk, Managam (Faculty of Engineering, Universitas Tanjungpura, 2020)
Inception of electrical treeingÂ can irreversibly deteriorate the insulation of polymeric power cables leading to a complete failure and initial process of degradation in polymer insulation due to a void that experiences high electric field stress in the material. This paper present will study fillerâ€™s influence on inception of electrical treeing growth in silicone rubber â€“ oil palm endokaprium composite.Â The observed data is inception voltage and time phenomena in two types of test sample, that is